Does total hip replacement affect sexual quality of life?. Issue 1 (December 2016) - Harmsen, Rita; Haanstra, Tsjitske; Sierevelt, Inger; Jansma, Elise; Nolte, Peter; Nicolai, Melianthe; Wall, Peter; Van Royen, Barend
Abstract Background Total Hip Replacement (THR) is an effective treatment for end-stage hip osteoarthritis. Since the introduction of total joint replacement, the effect on the Sexual Quality of Life (SQoL) following THR has been addressed in scant studies. The aim of our study was to systematically review the literature, to summarise effects of THR on patients' SQoL. Methods We searched PubMed, EMBASE and PsycINFO between January 1970 and February 9th, 2015 with search terms including Total Hip, Osteoarthritis, SQoL, and THR. Eligible studies were identified and two independent authors extracted data including details of SQoL, study quality and risk of bias. Results There were 12 eligible studies, which included a total of 2099 patients with an age range of 20–85 years. The methodological quality of ten studies was rated as low, and of two as moderate. Amongst the majority of patients, SQoL improved after surgery, both in terms of physical-functional and psychosocial well-being. However, changes between pre-operative and postoperative SQoL ranged extensively: for example, Sexual Dysfunction Δ 8–51 % and Sexual Activity (SA) Δ 0–77 %. Three studies reported that some patients never resumed SA again after surgery. Conclusion In over 40 years of THR treatment, scant studies have examined the effect of THR on patients' SQoL. This review suggests that SQol improves after THR, although the magnitude of effects varies highly. However, the quality of the supporting evidence was rated as low to moderate. This suggests a need for more high quality evidence about the effects of THR on SQoL.